Learning Through Crisis and Paradox in Justice-Oriented Teacher Education - Hilary E Hughes; Matthew Moulton; Gayle Andrews (Middle Grades Review, 2016)
In this article we explore some of the challenges, constraints, and what we refer to as glimmers of revelation that occurred during an experiential, community-based teacher education course that we designed and co-taught in spring 2015. Trying to take seriously Kumashiro’s (2009) notions that justice oriented teacher education happens “only when we ourselves are still struggling with questions about the ‘what else,’ ‘how else,’ and ‘where else’ that are involved” in this kind of teaching [emphasis added] (p. xxv), we explore moments where we grappled with the paradox, partiality, uncertainty, and discomfort (Kumashiro, 2009) that often accompany our commitments as middle grades teacher educators attempting to enact anti-oppressive teaching practices.